2013
DOI: 10.1111/maps.12238
|View full text |Cite
|
Sign up to set email alerts
|

Cathodoluminescence microscopy and spectroscopy of forsterite from Kaba meteorite: An application to the study of hydrothermal alteration of parent body

Abstract: Abstract-Highly forsteritic olivine (Fo: 99.2-99.7) in the Kaba meteorite emits bright cathodoluminescence (CL). CL spectra of red luminescent forsterite grains have two broad emission bands at approximately 630 nm (impurity center of divalent Mn ions) in the red region and above 700 nm (trivalent Cr ions) in the red-IR region. The cores of the grains show CL blue luminescence giving a characteristic broad band emission at 400 nm, also associated with minor red emissions related to Mn and Cr ions. CL color var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 39 publications
3
12
0
2
Order By: Relevance
“…Comparisons of the panchromatic CL images with high-resolution x-ray elemental area maps together with hyperspectral scans and individual spectra ( Fig. 2B and section S2) ( 13 15 ) reveal that panchromatic CL intensity in Mg-rich olivines is overwhelmingly controlled by their Al concentration: The higher the panchromatic CL intensity, the higher their Al concentration (section S2). In terrestrial olivines, Al occurs at minor to trace levels (tens to hundreds of parts per million), and Al in Mg-rich olivines in chondrules is highly variable with concentrations up to 0.6 weight % (wt %) Al 2 O 3 (table S1) ( 10 , 16 ).…”
Section: Resultsmentioning
confidence: 98%
“…Comparisons of the panchromatic CL images with high-resolution x-ray elemental area maps together with hyperspectral scans and individual spectra ( Fig. 2B and section S2) ( 13 15 ) reveal that panchromatic CL intensity in Mg-rich olivines is overwhelmingly controlled by their Al concentration: The higher the panchromatic CL intensity, the higher their Al concentration (section S2). In terrestrial olivines, Al occurs at minor to trace levels (tens to hundreds of parts per million), and Al in Mg-rich olivines in chondrules is highly variable with concentrations up to 0.6 weight % (wt %) Al 2 O 3 (table S1) ( 10 , 16 ).…”
Section: Resultsmentioning
confidence: 98%
“…The alteration could be analyzed by detailed mineral study of the meteorites and also by cathodluminescence method, as suggested recently (Gucsik et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the accumulation and release of the absorbed energy in the conditions of the increasing temperature of the substance (e.g., approach of a comet to the perihelion) may have either a synchronic or an asynchronic nature with a certain value of delay. In addition, the thermoluminescence spectra of a number of minerals, including forsterite, obtained by Koike et al (2002aKoike et al ( , 2002bKoike et al ( , 2006 with the first approach, are similar to the spectra of the cathodoluminescence of the same minerals (Gucsik et al 2013). The cathodoluminescence of the forsterite micrograins caused by fast-electron fluxes may also occur spectrally in the form of two bands of emission in the blue and red areas of the optical spectrum.…”
Section: Thermoluminescence Of Cosmic Substances -Astrophysical Projementioning
confidence: 54%